Механізми формування дисфункції жирової тканини на етапах розвитку метаболічного синдрому - Ларін, О. С.; Кирилюк, М. Л.; Третяк, О. Е.; Черенько, М. С.; Щекатурова, Л. В.; Горб, Н. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
It has been shown that the determination of the concentration of adiponectin blood levels and insulin resistance index is more informative method of assessment of the stage of development of the metabolic syndrome in obese people compared of the blood leptin concentration and BMI study.